Transformasi Pendidikan: Strategi Berkelanjutan untuk Kinerja Akademik Siswa - firda fina fitriya; Layli Rahmatillah (Yayasan Literasi Altruis Khatulistiwa, 2025)
This study aims to investigate the role of continuous improvement strategies in improving students' academic performance at MA Miftahul Ulum Gending, Probolinggo. A qualitative approach with a case study design was used to explore in depth the application of the concept of continuous improvement in the learning process. Data were collected through interviews with teachers and students, classroom observations, and analysis of learning documents. The results showed that giving students the freedom to choose learning materials and methods, active social interaction, and positive feedback from teachers and peers played an important role in increasing student motivation and engagement. This study concluded that continuous improvement, which is carried out continuously through evaluation and reflection, is effective in creating a more responsive learning environment and is oriented towards improving the quality of education. The application of technology in learning has also been shown to increase student engagement, by providing wider infrastructure and access to learning materials. Therefore, this study contributes to understanding how the concept of continuous improvement can be practically applied to improve students' academic performance.